2017
DOI: 10.1002/mmce.21145
|View full text |Cite
|
Sign up to set email alerts
|

A novel uniplanar antenna with dual wideband characteristics for tablet/laptop applications

Abstract: A novel uniplanar antenna design for tablet/laptop applications is proposed. The proposed antenna with a size of 68 × 12 × 0.8 mm3 is comprised of three strip sections, namely, the feeding strip, parasitic shorted strip, and tuning stub strip (or printed LC matching circuit). Five resonant modes are induced by the proposed antenna, and they are combined to yield two wide operating bands that have 6‐dB return loss bandwidths of more than 50% (695‐1190 MHz and 1690‐2930 MHz). Thus, the proposed antenna can easil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…From Table 5, it can be observed that the proposed antenna has the following features: Unlike to all existing state of arts, 1‐24 the proposed antenna is simple in design, compact and has dimensions of only 6 × 4 mm 2 , thus it can reduce the space required for mounting the antenna inside an actual laptop computers. Unlike those reported in References 16, 18, 19, the proposed antenna can operate within the desired bands of interest without using any additional lumped elements (inductors, capacitors etc. ), 3‐D structures and added holes or vias. Compared with References 1–5, 8, 9, 16, 18–20 the proposed antenna is suitable for different sizes of laptops and other portable devices. Unlike References 8, 9, 18, and the proposed antenna has exhibited broader fractional impedance bandwidths of 6.5% and 16% across the two operating bands. Compared with those in References 1, 4, 5, 11, 14, 21, 23, and the gain of the proposed antenna is above 3 dBi across all the operating bands. The proposed antenna can cover both the fundamental 2.4 and 5 GHz bands, unlike References 1–3, 7, 12. The proposed antenna does not require additional ground plane for affixing the antenna to system ground, unlike Reference 11 Unlike References 4, 5, 13, and the proposed antenna does not use expensive substrate. …”
Section: Performance Comparison Of Proposed Antenna With Other Pioneementioning
confidence: 98%
See 2 more Smart Citations
“…From Table 5, it can be observed that the proposed antenna has the following features: Unlike to all existing state of arts, 1‐24 the proposed antenna is simple in design, compact and has dimensions of only 6 × 4 mm 2 , thus it can reduce the space required for mounting the antenna inside an actual laptop computers. Unlike those reported in References 16, 18, 19, the proposed antenna can operate within the desired bands of interest without using any additional lumped elements (inductors, capacitors etc. ), 3‐D structures and added holes or vias. Compared with References 1–5, 8, 9, 16, 18–20 the proposed antenna is suitable for different sizes of laptops and other portable devices. Unlike References 8, 9, 18, and the proposed antenna has exhibited broader fractional impedance bandwidths of 6.5% and 16% across the two operating bands. Compared with those in References 1, 4, 5, 11, 14, 21, 23, and the gain of the proposed antenna is above 3 dBi across all the operating bands. The proposed antenna can cover both the fundamental 2.4 and 5 GHz bands, unlike References 1–3, 7, 12. The proposed antenna does not require additional ground plane for affixing the antenna to system ground, unlike Reference 11 Unlike References 4, 5, 13, and the proposed antenna does not use expensive substrate. …”
Section: Performance Comparison Of Proposed Antenna With Other Pioneementioning
confidence: 98%
“…This poses a good challenge to antenna designers in terms of design, fabrication, and reliability with respect to size, mounting, and cost. From the available open‐literature, extensive research work has been carried out on antenna miniaturization in terms of novel structures and antenna performances 1‐24 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Industrial Scientific Medical (ISM) bands, namely 2.4 GHz (2.40-2.48) GHz and 5 GHz (5.15-5.85) GHz are used in the WLAN/WiMAX environment. Therefore, multiband antennas including inverted-F [1,2], the coupled-fed planar inverted-F antennas in [3,4], branched monopole antenna [5], dual band monopole antenna [6], printed antenna [7], monopole antennas using reactive components [8,9], antennas using additional ground plane [10,11], meander antennas [12,13], folded antennas [14,15], uniplanar antennas in [16,17,18,19], broadband antenna [20], antennas having thickness of 1 mm [21,22,23,24] and cloverleaf-shaped monopole antenna [25] have been reported recently for WLAN/WiMAX technologies for the laptop computers. From the above mentioned antennas, it is understood that miniaturized and ultra-thin antennas showing high performance with less complex structure and covering WLAN/WiMAX bands for laptop applications are posing challenges for antenna designers due to shrinking of height and thickness of outside frame of the laptop display.…”
Section: Introductionmentioning
confidence: 99%